ELECTRONEUROMYOGRAPHIC PREDICTORS OF RECOVERY DURING RTMS-BASED REHABILITATION OF FACIAL NERVE NEUROPATHY - Khodjiyeva Dilbar Tadjiyevna; Kuliyev Husniddin Shamsevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Objective: To determine the value of electroneuromyographic parameters in monitoring recovery during rTMS-based rehabilitation. Methods: Distal latency, compound muscle action potential amplitude, motor unit potential duration, amplitude and phase number were compared across treatment groups. Results: The 10 Hz rTMS group showed the greatest reduction in distal latency and the largest increase in M- response amplitude. Conclusion: ENMG parameters provide objective biomarkers for treatment response and prognosis in facial nerve neuropathy.